2017
DOI: 10.1111/sji.12498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress and Antioxidant Status in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a common respiratory condition involving the airways and characterized by airflow limitation. Gaseous and noxious particles play an important role in this process. Antioxidants are the substances that may protect cells from the damage caused by unstable molecules known as free radicals. The increased oxidative stress in patients with COPD is the result of an increased burden of inhaled oxidants, as well as increased amounts of reactive oxygen species (ROS) genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 32 publications
1
47
2
1
Order By: Relevance
“…In human lungs, it is reported that oxidant-antioxidant imbalance is associated with airways obstruction, and altered oxidant-antioxidant balance in patients with COPD increases in parallel with the severity of the disease [ 21 ]. Repine et al reported that lipid peroxidation causes damage to multiple cell membrane components and impairs cell structure and permeability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human lungs, it is reported that oxidant-antioxidant imbalance is associated with airways obstruction, and altered oxidant-antioxidant balance in patients with COPD increases in parallel with the severity of the disease [ 21 ]. Repine et al reported that lipid peroxidation causes damage to multiple cell membrane components and impairs cell structure and permeability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COPD have higher levels of lipid peroxidation products in sputum [ 23 ], and serum levels of these products are higher in patients with severe airflow limitation compared with those with moderate limitation [ 24 ]. Based on these results, we suggest that bilirubin might protect the lungs by inhibiting lipid peroxidation [ 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include glutathione, glutathione peroxidase, superoxide dismutase, catalase, ferroxidase, and myeloperoxidase [43][44][45][46]. IMA is an oxidant marker resulting from the differentiation of albumin, with antioxidant properties, in situations involving increased oxidative stress [23].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes can either facilitate antioxidant reactions or directly decompose ROS [ 49 ]. GSH-Px and CAT play significant roles in peroxyl scavenging mechanisms and in maintaining the functional integration of cell membranes [ 50 ]. In addition, as the main product of lipid peroxidation, MDA is closely associated with pulmonary dysfunction and considered a biomarker in the assessment of lipid peroxidation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%